1997
DOI: 10.2172/554854
|View full text |Cite
|
Sign up to set email alerts
|

Thermal imaging measurement and correlation of thermal diffusivity in continuous fiber ceramic composites

Abstract: Continuous fiber ceramic matrix composites (CFCCs) are currently being developed for a variety of high-temperature applications, including use in advanced heat engines. For such composites, knowledge of porosity distribution and presence of defects is important for optimizing mechanical and thermal behavior of the components. The assessment of porosity and its distribution is also necessary during composite processing to ensure component unifo4ty. To determine the thermal properties of CFCC materials, and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 1 publication
(2 reference statements)
1
15
0
Order By: Relevance
“…The results showed that both plates were relatively homogeneous, with a thermal diffusivity of 0.97 mm2/s for the DCC specimen and 2.8 mm2/s for the DLC specimen. These values are consistent with those obtained for similar materials by Sun et al (1997 Fig. 7.…”
Section: Cfcc Specimenssupporting
confidence: 93%
“…The results showed that both plates were relatively homogeneous, with a thermal diffusivity of 0.97 mm2/s for the DCC specimen and 2.8 mm2/s for the DLC specimen. These values are consistent with those obtained for similar materials by Sun et al (1997 Fig. 7.…”
Section: Cfcc Specimenssupporting
confidence: 93%
“…The thermal imaging apparatus is comprised of a flash lamp system, an infrared camera, and a computer for data acquisition and processing. More information on this system can be found elsewhere 38 . The flash lamp system uses two standard photographic xenon flash-lamps to generate the thermal pulse.…”
Section: Infrared Thermal Imagingmentioning
confidence: 99%
“…The NDE data were presented as thermal diffusivity and ultrasonic transmission (UT) images mapping the entire liners (100% inspection). The data indicated that thermal diffusivity was affected slightly by local thickness variations, as an average thickness was used for each liner to derive the local thermal diffusivity (Sun et al, 1999). The outer liner was found to be generally uniform and free of defects from both thermal diffusivity and air UT tests.…”
Section: Nde Results Of Cfcc Linersmentioning
confidence: 99%
“…To determine their condition and assess operating damage, the liners were subjected to NDE at Argonne National Laboratory (ANL) during various processing stages, as well as before and after the engine test. The NDE techniques included pulsed infrared thermal imaging, aircoupled ultrasonic scanning, and X-ray CT (Sun et al, 1998(Sun et al, , 1999Sun, 2001). This paper presents the NDE results for the CFCC liners before and after the EBC application and after the engine test.…”
Section: Introductionmentioning
confidence: 99%